An Analysis of Secondary Mathematics Teacher Learning in the Midwest Master Teacher Partnership - (:unkn) unknown (My University, 2023)
This case study investigates the professional learning and changes in teaching practices and leadership of four experienced, mid-career secondary mathematics teachers as a result of participation in the Midwest Master Teacher Partnership, a professional development partnership between a research university and a large, urban school district. The design of the professional development was based primarily on teacher action research; it placed the teacher at the center of the learning experiences, and included considerations of teachers’ existing knowledge, contexts, community, and assessment.The primary research question is, “How have teachers’ practices changed through their participation in a practice-based professional development project?” To answer this question, this study considers three aspects of teacher learning and practice: (1) The trajectories of teachers’ changes in practice and the way the nature of their participation in MMTP impacted their pedagogical practice; (2) The evolution of teachers’ mathematical knowledge for teaching and beliefs about teaching mathematics over the course of MMTP; and (3) The pathways that teachers took in their professional learning with MMTP, the factors that shaped their movement on the pathways, and ways that the nature of their participation in MMTP impacted teachers’ attitudes toward professional development and their thoughts about future engagement in professional learning. A qualitative analysis was performed on written, video recorded, and audio recorded artifacts collected over the duration of the Midwest Master Teacher Partnership and the teachers’ work was examined for changes in knowledge, beliefs, and teaching practices over time. The findings provide evidence that the four teachers each experienced individual changes in practice: changing notions of student success, building trust in students to take ownership over their learning, building a community of learners, and changing beliefs about students and how they learn. In addition, the four teachers each experienced individual changes leadership: establishing credibility, sharing knowledge with the larger community, gaining confidence as an expert, and shared leadership and collective vision. This case study demonstrates that consideration of experienced teachers needs when planning and implementing practice-based professional development and using teacher action research to drive teacher learning can promote productive changes in teachers’ mathematical knowledge for teaching, teaching practices, and beliefs about teaching and learning.